Usaha Meningkatkan Hasil Belajar Revolusi Menegakkan Panji-Panji NKRI dengan Menggunakan Model Pembelajaran NHT pada Siswa XI MIA SMA Negeri 2 Tambun Utara - Rita Yulismar (ISTORIA: Jurnal Pendidikan dan Sejarah, 2017)
AbstractOne of the actions taken by the government to improve the quality of education is to make a paradigm shift that changes the orientation of learning into learning centered on learners. In this lesson, teachers are expected to be facilitators who facilitate learners in learning, and learners must actively learn from various learning sources and work with their friends. One model of learning that can be applied is the learning model NHT (Number Head Together).The formulation of this research problem is whether the use of NHT method in learning History of Revolution's material Enforcing Panji-Panji NKRI can increase interest and learning outcomes XI MIA 1 SMA Negeri 2 Tambun Utara, North Tambun district, Bekasi district, West Java.The results of this study can be concluded that the implementation of NHT learning model can improve the learning outcomes Revolusi Upholding Panji NKRI in class XI MIA 1 SMA Negeri 2 Tambun Utara, North Tambun district. This can be shown by the increasing number of students who complete the study of 18 students or 42.86% in pre cycle to 29 students or 69.05% in cycles I and 41 students or 92.86% in cycle II. Keywords: learning outcomes, NH learning model, N 2 Tambun Utara high school students